A new species of Lamiogethes and a new species of Meligethes from China (Coleoptera: Nitidulidae: Meligethinae) - Chen, Ying; Lin, Xiaoli; Huang, Min; Yang, Xing Ke (Zootaxa, 2015)
A new species of Lamiogethes Audisio & Cline, 2009, L. nyingchiensis sp. nov., and a new species of Meligethes Stephens, 1830, M. (Odontogethes) scrobescens sp. nov. are described and illustrated from China. The differences between these new species and closely related species are discussed. The materials examined are deposited in the Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZAS).